Colonoscopy Versus Fecal Occult Blood Test Versus No Screening. - Sergeev, D.; Heisser, T.; Hoffmeister, M.; Brenner, H. (Deutsches Ärzteblatt International, 2026)
Background: Colorectal cancer (CRC) remains a leading cause of cancer-related death. Many of these deaths could be prevented by screening. The German screening program was updated in April 2025, enabling men and women aged 50 and above to choose between fecal immunochemical testing (FIT) once every two years or up to 2 screening colonoscopies (CS) at an interval of 10 years apart. In this study, we compare the expected long-term outcomes for these strategies as well as for a combination of the two, assuming that full use is made of the tests that are offered. Methods: We used COSIMO, a validated multi-stage simulation model for CRC, to assess expected outcomes assuming full adherence for simulated cohorts of 100 000 men and women aged 50–85. We calculated and compared the expected cumulative numbers of CRC cases and CRC-related deaths with FIT-based screening, colonoscopy-based screening, and no screening. Results: On the assumption of full adherence, the two screening strategies yielded similar reductions of CRC case numbers (69% for FIT, 77% for CS) and deaths from CRC (82% for both). Even stronger reductions were found if CS at age 50 and 60 was followed by FIT at ages 70, 72, and 74 (81% reduction in CRC cases, 89% reduction in deaths from CRC). Conclusion: The two screening strategies currently offered in Germany are highly effective to a similar extent. Our analysis yields relevant information for informed choices between the alternative screening offers.